Determinants and Long‐Term Effects of Attendance Levels in a Marital Enrichment Program for African American Couples. (27th April 2015) - Barton, Allen W.; Beach, Steven R. H.; Hurt, Tera R.; Fincham, Frank D.; Stanley, Scott M.; Kogan, Steven M.; Brody, Gene H.
Abstract : Although most efficacious marital enrichment programs are multisession, few studies have explored whether outcomes differ according to session attendance, particularly among minority groups with lower than average participation in prevention programs. This study therefore investigates attendance levels and long‐term improvements in couple functioning among 164 couples participating in the Promoting Strong African American Families program. Structural equation models indicated session attendance predicted 2‐year changes for men's reports of communication, commitment, and spousal support (marginally) but not for women's. Individual and couple characteristics that predicted attendance levels were also identified. Results highlight distinct gender differences in the effects of sustained attendance as well as characteristics that provide early identifiers for African American couples at increased risk of low program attendance.